Travel : Then and Now - Kalman, Bobbie (St. Catherines, ON : Crabtree Publishing Company, 2014)
"From wagons and steamboats to hybrid cars and ferries, all modes of transportation have changed significantly over time. Historical photographs and accessible text combine to help young readers compare and contrast transportation from past to present."--
How do you travel? -- Animal power -- Moving to new homes -- Traveling on water -- Trains then and now -- Cars and trucks -- City travel -- Traveling in winter -- Up in the air -- Where would you go? -- Learn more.
Includes bibliographical references (page 23) and index.
Guided Reading: M.
5-8
K to grade 3
University of Alberta copy in the Canadian Children's Book Centre Depository Collection.
Keywords: Transportation -- History -- Juvenile literature